Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Motivasi Kerja Guru Di Sma Negeri 1 Ambon Kecamatan Sirimau Kota Ambon - Wan Tamalane; Therisia Laurens; Jan Eduard Lekatompessy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Education is a critical future investment for developing countries, including Indonesia. According to the 1945 Constitution, Indonesia aims to enlighten the nation's life, emphasizing the importance of every citizen receiving quality education without discrimination. This study highlights the role of school principals as vital leaders in the effectiveness of educational institutions, particularly in enhancing teacher motivation. Using a qualitative method, this research was conducted at SMA Negeri 1 Ambon to explore and examine the factors influencing leadership roles and teacher motivation. The results indicate that principals play multifunctional roles in management, administration, public relations, decision-making, supervision, motivation, and innovation. Effective principals can create a conducive learning environment, improve teacher performance, and ultimately contribute to the overall improvement of education quality. Teacher motivation is also found to be significantly influenced by the principal's role, who actively provides guidance, support, and professional development opportunities. This study provides insights into effective strategies for improving education quality through strong and inspiring school leadership.